A Study On Mechanical Properties Of 3d Printed Hybrid Polymer Composites (Journal of Namibian Studies : History Politics Culture, 2023)
The use of 3D printing has gained significant popularity for producing functional components, ranging from prototypes and membranes to shields and sports wearables. As this method becomes more prevalent, there is a growing need to address challenges related to the limitations of suitable printing materials compared to traditional materials. Innovative methods for simulating failures in 3D-printed cellular structures have been developed to emphasize the impact of various process variables. The scarcity of appropriate printing materials can be attributed to the constraints of 3D printing techniques in accommodating a diverse range of materials. Over the past decade, 3D printing technologies have found extensive application across industries, including the military, serving as a rapid prototyping, and manufacturing method. However, commercially available printing polymers have exhibited inherently lower mechanical properties, such as strength and stiffness, when compared to traditional manufacturing materials. To overcome these limitations, multi-material additive manufacturing (AM) technology has emerged as a promising alternative. This approach allows for the creation of complex structures with a broad spectrum of mechanical characteristics, presenting a significant advancement over traditional assembly methods. In ongoing efforts to enhance material qualities, there is a current focus on fabricating polymer composites using 3D printing techniques. Various reinforcement materials, including carbon fibers and multi-walled carbon nanotubes (MCNTs), are being incorporated into matrix materials like ABS and PETG. This endeavor aims to exploit the capabilities of 3D printers to innovate and create complex items with improved material properties, opening the door to further research and development in fast manufacturing processes.